Figurative Language Analysis in Devil May Cry V Original Soundtrack - Wijaya, Abraham Louise; Sukesi, Erni; Damayanti, Indah (UNIB Press, 2025)
This research aimed to find figurative language items from 12 types of figurative language from the source material in 4 different character theme songs. This research implements the qualitative research methods by collecting the data through the triangulation method and inductive data analysis which is based on Sugiyono's (2015). The data findings were collected through the song lyrics while taking note of the samples in the lyrics text and anatomizing differences in figurative type from the media finally, they were sorted into the checklist table to simplify the findings and classify types of figurative that are being used. The results showed that: 1) the number of figurative that are being used in 12 different figurative language types is 126 items with the first song having 45 items, the second song having 19 items, the third song has 40 items, and lastly the fourth song has 22 items. 2) from the first song to the fourth song there are similes with 1 item, personification with 21 items, metonymy with 19 items, apostrophe with 12 items, hyperbole with 26 items, synecdoche with 13, irony with 7 items, oxymoron with 10 items, antithesis with 6 items, alliteration with 8 items, and lastly paradox with 3 items. 3) the most used figurative language type in four songs is Hyperbole, which consists of 26 items. The fewest figurative language types used are similes with 1 item and can only be found in the first song. However, there is one figurative language type that is not included which is a metaphor.